The puzzle of orofacial pain integrating research into clinical management - Türp, Jens Christoph 1960-; Sommer, Claudia; Hugger, Alfons 1966- (Pain and headache, 2007)
In recent years, progress in pain research has yielded substantial new insights, and this has profoundly altered our understanding of various orofacial pain conditions. Written by renowned international researchers and clinicians, this state-of-the-art textbook presents recent advances in the understanding of orofacial pain and offers evidence-based management approaches, thus bridging the gap between timely research findings and daily clinical practice. The reader is provided with helpful in-depth information of up-to-date advances in basic research as well as with the present knowledge of the pathophysiology, diagnosis and management of the five most common orofacial pain conditions. In addition, the psychosocial impact of orofacial pain in daily life and future developments are presented. Health care professionals, such as dentists, neurologists, physicians as well as students will find this volume helpful and valuable for an advanced understanding of the diverse orofacial pain conditions and for the improvement of patient care